Indebtedness in the EU: A drag or a catalyst for growth? - Alina Mika; Tina Zumer (European Central Bank (ECB), 2017)
We study the relationship between debt and growth in EU countries in the years 1995-2015. We investigate the debt-growth nexus in two alternative empirical set-ups: the traditional cross-county panel regressions and mean group estimations. We find evidence of a positive long-run relationship between private sector indebtedness and economic growth, and a negative relationship between public debt and long-run growth across EU countries. However, the more immediate impact of private sector debt on growth is found to be negative, and positive for the public sector debt. We find no conclusive evidence for a common debt threshold within EU countries, neither for the private nor for the public sector, but some indication of a non-linear effect of household debt.
Keywords: O47; N14; H60; 330; debt; threshold; panel; European Union countries; cross-sectional dependence